Studies of magnetic properties of EuSnP single crystals - Karolina Podgórska; Kamila Komędera; Janusz Przewoźnik; Łukasz Gondek; Czesław Kapusta; Wojciech Tabiś; Michał Babij; Lan Maria Tran; Damian Rybicki (Scientific Reports)
Abstract Europium-based compounds exhibit a wide range of intriguing properties due to the element’s ability to exist in two valence states: Eu $$^{2+}$$ , which carries a strong magnetic moment, and non-magnetic Eu $$^{3+}$$ , as well as due to interactions between localized f-electrons and conduction electrons. In this work, we present a comprehensive study of EuSnP single crystals using X-ray diffraction, heat capacity, dc and ac magnetic susceptibility, magnetization, and Mössbauer spectroscopy measurements. EuSnP undergoes an antiferromagnetic transition at $$T_\text {N}=21$$ K. However, our results indicate that magnetic correlations emerge well above the transition temperature. Mössbauer spectroscopy revealed that Eu valence in EuSnP is 2+ contradicting earlier suggestions of its mixed-valent state. It also shows exceptionally high values of the effective magnetic field (39 T) and large electric field gradient at Eu nuclei likely due to the short distances between Eu atoms and their nearest neighbors. Based on our studies, we propose two possible magnetic ordering schemes of Eu magnetic moments. In the first one, moments are aligned ferromagnetically within each Eu-P plane and there is an antiferromagnetic coupling between Eu-P planes forming a bilayer. In the second one, there is a ferromagnetic order within the entire bilayer and neighboring bilayers are coupled antiferromagnetically. In both scenarios magnetic moments are oriented along or close to the crystallographic c-axis.